2022
DOI: 10.3390/ma15238662
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical Impact of Loss of an Implant in the Treatment with Mandibular Overdentures on Four Nonsplinted Mini Dental Implants: A Finite Element Analysis

Abstract: The aim of this study was to evaluate the biomechanical impact, in terms of stress and displacement, at the level of a mandibular overdenture, on four mini dental implants (MDIs) after the loss of an implant. A three-dimensional virtual model was obtained by scanning the overdenture, and a biomechanical analysis was carried out, using the finite element method (FEM). The displacements of the overdenture and the equivalent von Mises stresses were evaluated using logarithmic scales. In the case of a mandibular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…The differences between the results of this study and other studies on biomechanical behavior [37,38,[47][48][49][50][51][52][53][54] may be due to different mini-implant materials (Ti-Zr vs. Ti-Al6-V4), different retention mechanisms (Optiloc ® Retentive System vs. "O"-ring), different implant designs and neck widths [55], different dimensions of implants [56,57], small differences in strain measurements and different residual ridge forms. We bonded strain gauges as close as possible to the implant-bone interface due to the assumption that stress and strains would be highest where two materials with different stiffnesses meet.…”
Section: Discussioncontrasting
confidence: 83%
“…The differences between the results of this study and other studies on biomechanical behavior [37,38,[47][48][49][50][51][52][53][54] may be due to different mini-implant materials (Ti-Zr vs. Ti-Al6-V4), different retention mechanisms (Optiloc ® Retentive System vs. "O"-ring), different implant designs and neck widths [55], different dimensions of implants [56,57], small differences in strain measurements and different residual ridge forms. We bonded strain gauges as close as possible to the implant-bone interface due to the assumption that stress and strains would be highest where two materials with different stiffnesses meet.…”
Section: Discussioncontrasting
confidence: 83%
“…Still, the primary disadvantage of this approach is the reduced surface contact with the surrounding bone (i.e., lesser mechanical strength to functional loading) [42,43] and the limited surface area of small-diameter implants (i.e., less resistance to occlusal forces) [44,45]. However, Teodarescu et al demonstrated that a sufficient number of mini-implants and a functional topographical distribution based on biomechanical masticatory forces could prevent these mechanical challenges [46]. Also, Chatrattanarak et al found that the configuration of two mini-implants supporting mandibular overdentures with an immediate loading approach had a significantly higher success rate, cost effectiveness, and patient satisfaction after eight years of follow-up compared to four mini-dental implant-retained mandibular overdentures [7].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many studies used FEA to reduce overload before implant placement. Most studies conduct stress analysis based on new implants [48,49], changes in implant materials [50][51][52], and various variables [53]. Although this can achieve better implants and placement plans, it does not help with real-time placement depending on the condition of the patient.…”
Section: Summary Remarks and Conclusionmentioning
confidence: 99%